The interrelationship among bank profitability, bank stability, and loan growth: Evidence from Vietnam - Tu DQ Le (Cogent Business & Management, 2020)
This study investigates the interrelationship among bank stability, profitability, and loan growth in the Vietnamese banking system between 2006 and 2017 using a simultaneous equations model. The findings show the bidirectional links between these variables. More specifically, bank profitability is positively associated with bank stability and vice versa. Loan growth is negatively related to bank stability and vice versa. Also, the findings show a positive interrelationship between bank profitability and loan growth. Nonetheless, these findings suggest the trade-off benefit of pursuing massive loan growth by banks. Nonetheless, our research has implications for bank supervisors, policy-makers, and bank managers.
Keywords: G21; G28; G30; 650; bank stability; profitability; loan growth; Vietnam; simultaneous equations model